Improving the performance of motor drive servo systems via composite nonlinear control - Guoyang Cheng; Wentao Yu; Jin-gao Hu (CES Transactions on Electrical Machines and Systems, 2018)
This paper presents a discrete-time design of robust composite nonlinear controller to achieve fast and accurate set-point tracking for motor servo systems subject to actuator saturation and disturbances. The basic idea here is to use a combination of linear and nonlinear control, together with a disturbance rejection mechanism based on extended state observer. The linear control part is designed to yield a fast response, and the nonlinear part serves to reduce the overshoot, while the extended state observer estimates simultaneously the state vector and the unknown disturbance for control and compensation. The closed-loop stability is analyzed using the Lyapunov theory. Practical application in a permanent magnet synchronous motor position servo system is given to demonstrate the effectiveness of the proposed control scheme.